Frontispiece: From LiB3O5 to NaRbB6O9F2: Fluorine‐Directed Evolution of Structural Chemistry. Issue 40 (18th July 2018) - Han, Shujuan; Zhang, Bingbing; Yang, Zhihua; Pan, Shilie
Abstract : Introducing fluorine into borates indicates the direction for structural evolution. By taking the famous LiB3 O5 as a maternal structure, using F atoms to substitute O atoms, as well as cation substitution strategy, in their Communication on page 10022 ff., Z. Yang, S. L. Pan et al., describe the successful design and synthesis of a new member of fluorooxoborates, NaRbB6 O9 F2 with a unique [B6 O9 F2 ]∞ layer. Its discovery enriches the structural chemistry of borates.